Similarities and Differences in the GFP Movement in the Zygotic and Somatic Embryos of Arabidopsis - Godel-Jędrychowska, Kamila; Kulińska-Łukaszek, Katarzyna; Kurczyńska, Ewa (Frontiers in Plant Science, 2021)
Intercellular signalling during embryo patterning is not well understood and the role of symplasmic communication has been poorly considered. The correlation between the symplasmic domains and the development of the embryo organs/tissues during zygotic embryogenesis has only been described for a few examples, including Arabidopsis. How this process occurs during the development of somatic embryos (SEs) is still unknown. The aim of these studies was to answer the question: Do SEs have a restriction in symplasmic transport depending on the developmental stage that is similar to their zygotic counterparts? The studies included an analysis of the GFP distribution pattern as expressed under diverse promoters in zygotic (ZEs) and SEs. The results of the GFP distribution in the ZEs and SEs showed that 1/ the symplasmic domains between the embryo organs and tissues in the SEs was similar to those in the ZEs and 2/ the restriction in symplasmic transport in the SEs was correlated with the developmental stage and was similar to the one in their zygotic counterparts, however, with the spatio-temporal differences and different PDs SEL value between these two types of embryos.